MENDEKATKAN SISWA DENGAN KEARIFAN BUDAYA LOKAL MELALUI IPS DI SEKOLAH DASAR - Sekar Purbarini Kawuryan (MAJALAH ILMIAH PEMBELAJARAN, 2010)
any preservation from their community. Slowly but sure, the process will be pass through the extinction. One way to guard against globalization is using the utilization of local culture potentials in learning process on school. Social studies which hands on as a significant lesson to improve culture, hopefully could use local culture potentials as well as possible. Social studies in elementary school should develop all capability of students, especially how to keep up with society around they live. Because of that, there are necessary to prepare and have many teachers who possess sufficient comprehension about local culture, besides their responsibility in material lesson.